Sociomateriality and Organizational Analysis: from Rhetoric to Relevance - Holz, Edvalter Becker (Organizações & Sociedade, 2021)
This essay expands upon the debate on sociomateriality with a critique of the current ontological agenda. Based upon the influential literature from the fields of management and organization studies, and information systems, it presents the emergence, the development, the consolidation and the popularization of the debate on the relations between the social and the material in organizations. Drawing on this trajectory, the paper suggests that the current agenda for a sociomaterial ontology is constituted predominantly through rhetorical uses of the notion of ontology. The relevance of this contribution lies in questioning the supposed development of a sociomaterial ontology, describing and exemplifying its rhetorical strategies: authorial randomness, theoretical centrifugation, and conceptual procrastination. It concludes that it is necessary to return to the phenomenon as relevant “in” the debate from the point of view of its trajectory: the diffusion of new technologies and the subsequent implications at the organizational and social levels. The main implication for future research is the adoption of pragmatic ontologies with the aim of restoring the primacy of the phenomenon over the ontology.